2022
DOI: 10.1002/adfm.202204558
|View full text |Cite
|
Sign up to set email alerts
|

Magnetothermal Modulation of Calcium‐Dependent Nerve Growth

Abstract: Nerve injuries are common, and the available treatments including invasive surgeries do not guarantee complete regeneration of the injured nerves and restoration of function. Despite the ability of peripheral nerves to regenerate, the slow rate of axonal growth hampers the functional recovery. Development of new approaches to discover underlying mechanisms that may accelerate axonal growth is needed to overcome these limitations and augment available treatments of nerve injury. In addition to chemical factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This transgene‐free magneto‐thermally controlled release of adrenal hormones will no doubt precipitate advances in understanding the biology of stress and in developing treatments for stress‐related psychiatric disorders. It certainly seems that other hormones in other TRPV1‐expressing organs can be similarly regulated by MNMs‐based stimulation methods without involving gene transfection, offering potential for future clinical use (Maeng et al, 2022; Rosenfeld et al, 2022).…”
Section: Mnms‐mediated Neuromodulationmentioning
confidence: 99%
“…This transgene‐free magneto‐thermally controlled release of adrenal hormones will no doubt precipitate advances in understanding the biology of stress and in developing treatments for stress‐related psychiatric disorders. It certainly seems that other hormones in other TRPV1‐expressing organs can be similarly regulated by MNMs‐based stimulation methods without involving gene transfection, offering potential for future clinical use (Maeng et al, 2022; Rosenfeld et al, 2022).…”
Section: Mnms‐mediated Neuromodulationmentioning
confidence: 99%
“…By converting magnetic fields into thermal signals, magnetic nanoparticles (MNPs) have opened up possibilities for non-invasive neural thermal stimulation techniques with highly precise nanoscale spatial resolution. 210 The heating effect of MNPs is caused by the work done by magnetic torque on the dissipative forces during the cyclic response of magnetization. 211 Ranging from 100 kHz to 1 MHz, 212 the hysteresis-heating alternating field is the most widely used magnetic field.…”
Section: Functional Material-mediated Wireless Physical Signals For N...mentioning
confidence: 99%
“…211 Ranging from 100 kHz to 1 MHz, 212 the hysteresis-heating alternating field is the most widely used magnetic field. 210 When MNPS are exposed to alternating magnetic fields (AMFs), the heat is dissipated arising from thermodynamic irreversibility, making them suitable for mediating magneto-thermal stimulation. 213 Magneto-thermal stimulation through MNPs can activate thermosensitive ion channels, such as TRPV1 and anoctamin1, to induce ion exchange in neurons, thus modulating neural activity.…”
Section: Functional Material-mediated Wireless Physical Signals For N...mentioning
confidence: 99%
“…It is reported that the formation of the growth cone influenced by the calcium levels of cells via regulation of the secretion of netrin-1 and BDNF. For example, the axonal growth can be accelerated by TRPV1-mediated Ca 2+ influx and thus activating the protein kinase A pathway . Cell fate is decided by the key cellular processes related to signaling and gene expression.…”
Section: Photosignal Transduction In Neuronsmentioning
confidence: 99%
“…For example, the axonal growth can be accelerated by TRPV1mediated Ca 2+ influx and thus activating the protein kinase A pathway. 97 Cell fate is decided by the key cellular processes related to signaling and gene expression. Biomaterial substrates provide a promising way to mimic the natural biological microenvironment to active the components cell membrane, modulate neural signals.…”
Section: Photosignal Transduction In Neuronsmentioning
confidence: 99%